2018
DOI: 10.22146/agritech.22451
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Fisikokimia Yogurt Tanpa Lemak dengan Penambahan Whey Protein Concentrate dan Gum Xanthan

Abstract: Non-fat yogurt exhibited weak body, poor texture, and whey separation because of reduction of fat. The separation of whey in yogurt is not desired by consumer. The aim of present study was to evaluate the effect of adding whey protein concentrate (WPC) and xanthan gum on physical, chemical and sensory properties of non-fat yogurt. Physical and chemical properties were tested using randomized block design whereas the yogurts properties during 21 days of cold storage included syneresis index and organoleptic. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
6
0
5
Order By: Relevance
“…Sineresis pada yoghurt merupakan fenomena pemisahan whey dari koagulan yoghurt (Tamime & Robinson, 2007). Sineresis terjadi karena adanya penyusutan struktur tiga dimensi dari jaringan protein yang menyebabkan turunnya kekuatan ikatan whey protein sehingga terpisah dari yoghurt (Djali, 2018). Manab (2008), menjelaskan bahwa terjadinya sineresis kemungkinan disebabkan oleh perubahan kelarutan kasein dan pengkerutan partikel kasein.…”
Section: Sineresisunclassified
“…Sineresis pada yoghurt merupakan fenomena pemisahan whey dari koagulan yoghurt (Tamime & Robinson, 2007). Sineresis terjadi karena adanya penyusutan struktur tiga dimensi dari jaringan protein yang menyebabkan turunnya kekuatan ikatan whey protein sehingga terpisah dari yoghurt (Djali, 2018). Manab (2008), menjelaskan bahwa terjadinya sineresis kemungkinan disebabkan oleh perubahan kelarutan kasein dan pengkerutan partikel kasein.…”
Section: Sineresisunclassified
“…Whey yang terpisah dari yoghurt akan menimbulkan sineresis (Djali et al, 2018). Hasil penelitian menunjukkan sineresis yoghurt dengan penambahan CMC pada susu sapi segar memiliki kisaran 6,83 -40,76%, susu UHT low fat sebesar 1,80 -26,37%, susu UHT full fat sebesar 0,59 -20,45%.…”
Section: Sineresisunclassified
“…Susu UHT low fat memiliki kandungan lemak yang rendah hal ini membuat total padatan menjadi rendah dibandingkan dengan susu sapi segar. Menurut Djali et al (2018), bahwa komponen lemak yang rendah pada susu akan mengurangi total padatan sehingga memberikan tekstur yang kurang diinginkan dan meningkatkan kemungkinan pemisahan whey.…”
Section: Kadar Airunclassified
“…The results of statistical analysis of variance on the consistency of yogurt showed that the panelists preferred the highest level of preference to yogurt with the addition of dadih with a concentration of 10% (v / v) with an average value of 2.6. Djali et al (2018) stated that the increased amount of protein causes the formation of coagulants hence yogurt has a higher consistency. The results of the analysis of variance showed that there was a significant difference (P <0.05) in all variations in the concentration of yoghurt.…”
Section: Hour 48 Hour Hour 48 Hourmentioning
confidence: 99%